Review of Islamic Law Regarding the Marriage of Pregnant Women Out of Wedlock and the Status of Their Children - Gunawan Gunawan; Sainun Sainun; Gazali Gazali (JURNAL PENDIDIKAN IPS, 2024)
In the Iptek era, the use of medsos could hardly be restricted because it crossed space, time, and place, so that the Islamic community was increasingly confronted with various issues, whether directly touching the doctrine of Islam or other problems that still had to do with Islam, and the issue needed instruments of solution, and one of those instruments was Islamic law. One of the issues that is currently happening is the free association of young people who not only meet in person but have spread to social media such as Facebook, Whatsapp, Instagram, and so on that is increasingly facilitating meetings. So many things are emerging that should not happen in the Islamic generation, just say, for example, dating and up to having pre-marriage sex that causes pregnancy outside the marriage, which the impact is not good for the personal and society, so become a material gunjing because of marriage due to the occurrence of pregnancies outside the wedding, and the problem does not stop there; it continues until the status of the child is born. This study aims to explain in depth the relationship between the law of marriage in pregnancy and the status of the child born, taking into account the different opinions among scholars and based on the fatwa of the scholar's assembly contained in the Book of Compilation of Islamic Law.